Combination of Coenzyme Q10 Intake and Moderate Physical Activity Counteracts Mitochondrial Dysfunctions in a SAMP8 Mouse Model. (24th October 2018) - Andreani, C.; Bartolacci, C.; Guescini, M.; Battistelli, M.; Stocchi, V.; Orlando, F.; Provinciali, M.; Amici, A.; Marchini, C.; Tiano, L.; Orlando, P.; Silvestri, S.
Abstract : Aging skeletal muscles are characterized by a progressive decline in muscle mass and muscular strength. Such muscular dysfunctions are usually associated with structural and functional alterations of skeletal muscle mitochondria. The senescence-accelerated mouse-prone 8 (SAMP8) model, characterized by premature aging and high degree of oxidative stress, was used to investigate whether a combined intervention with mild physical exercise and ubiquinol supplementation was able to improve mitochondrial function and preserve skeletal muscle health during aging. 5-month-old SAMP8 mice, in a presarcopenia phase, have been randomly divided into 4 groups (n = 10 ): untreated controls and mice treated for two months with either physical exercise (0.5 km/h, on a 5% inclination, for 30 min, 5/7 days per week), ubiquinol 10 (500 mg/kg/day), or a combination of exercise and ubiquinol. Two months of physical exercise significantly increased mitochondrial damage in the muscles of exercised mice when compared to controls. On the contrary, ubiquinol and physical exercise combination significantly improved the overall status of the skeletal muscle, preserving mitochondrial ultrastructure and limiting mitochondrial depolarization induced by physical exercise alone. Accordingly, combination treatment while promoting mitochondrial biogenesis lowered autophagy and caspase 3-dependent apoptosis. In conclusion, the present study shows that ubiquinol supplementation counteracts the deleterious effects of physical exercise-derived ROS improving mitochondrial functionality in an oxidative stress model, such as SAMP8 in the presarcopenia phase.